Language lateralisation measured across linguistic and national boundaries. (February 2019) - Hausmann, Markus; Brysbaert, Marc; van der Haegen, Lise; Lewald, Jörg; Specht, Karsten; Hirnstein, Marco; Willemin, Julie; Barton, Jack; Buchilly, Delia; Chmetz, Florian; Roch, Maja; Brederoo, Sanne; et al.
Abstract: The visual half-field technique has been shown to be a reliable and valid neuropsychological measurement of language lateralisation, typically showing higher accuracy and faster correct responses for linguistic stimuli presented in the right visual field (RVF) than left visual field (LVF). The RVF advantage corresponds to the well-known dominance of the left hemisphere (LH) in processing language(s). However, clinical and experimental neuroscientists around the globe use different variations of the visual half-field paradigm, making direct comparisons difficult. The current study used a word/non-word visual half-field paradigm with translingual stimuli. In total, 496 participants from seven European countries were investigated: Belgium (64), England (49), Germany (85), Italy (34), The Netherlands (87), Norway (51), and Switzerland (126), covering six international languages (Dutch, English, French, German, Italian, Norwegian). All language groups revealed a significant RVF/LH advantage in accuracy and reaction times that accounted for up to 26.1% of the total variance in performance. We found some variation in the degree of the RVF/LH advantage across language groups, accounting for a maximum of 3.7% of the total variance in performance. The RVF/LH advantage did not differ between subsamples speaking English, French or German as first or second languages or between monolingual and early/late bi/multilinguals. The findings suggest that the translingual lexical decision task (TLDT) is a simple but reliable measurement of language lateralisation that can be applied clinically and experimentally across linguistic and national boundaries.